2000
DOI: 10.1080/00365590050509913
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Squamous Cell Carcinoma of the Penis

Abstract: Objective: To review the epidemiology of invasive cancer of the penis based on scientific publications identified by a Medline search from 1966-2000 for the keywords penis/penile, cancer/carcinoma and risk as well as the cited references in the identified papers. Results: Strong risk factors (OR >10) identified by case-control studies included phimosis, chronic inflammatory conditions such as balanopostitis and lichen sclerosus et atrophicus and treatment with psoralen and ultraviolet A photochemotheraphy (PUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
180
0
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(195 citation statements)
references
References 53 publications
1
180
0
14
Order By: Relevance
“…Among discordant sites that showed increased risks among spouses, sexual and smoking habits were the likely reason for the associations found in Table 1. Human papilloma virus (HPV) infection is the main etiological factor for cervical cancer and it is also strongly indicated in penile cancer (Dillner et al, 2000;Zur Hausen, 2000). The SIRs between these two cancers were the highest noted for the whole study, over 1.8.…”
Section: Discussionmentioning
confidence: 94%
“…Among discordant sites that showed increased risks among spouses, sexual and smoking habits were the likely reason for the associations found in Table 1. Human papilloma virus (HPV) infection is the main etiological factor for cervical cancer and it is also strongly indicated in penile cancer (Dillner et al, 2000;Zur Hausen, 2000). The SIRs between these two cancers were the highest noted for the whole study, over 1.8.…”
Section: Discussionmentioning
confidence: 94%
“…Only a few studies are reported on penile cancer and the role of HPV; a review is given by Griffiths and Mellon (1999) and later by Dillner et al (2000). The prevalence of subclinical or latent penile HPV infections among young, sexually active and healthy individuals is reported between 20 and 50%, while the incidence of penile carcinoma is relatively low (Van Doornum et al, 1994;Wikström et al, 2000).…”
Section: Penile Carcinomamentioning
confidence: 99%
“…Presence of HPV DNA in carcinomas of the penis is observed in a proportion of the specimens analysed (Grussendorf-Cronen, 1997;Tornesello et al, 1997;Dianzani et al, 1998;Levi et al, 1998;Poblet et al, 1999;Dillner et al, 2000;Rubin et al, 2001). Some serological studies relative to HPV infection in individuals with penile carcinoma were carried out in relatively small groups of patients (Wideroff et al, 1996b;Strickler et al, 1998;Carter et al, 2001).…”
mentioning
confidence: 99%
“…Males deserve access to a vaccine that can prevent the majority of cases of genital warts, especially considering that males often suffer longer duration of genital warts and incur greater treatment costs than females [49]. Furthermore, HPV is responsible for a wide range of cancers including 70-100 percent of penile intraepithelial neoplasia and 40-50 percent of all invasive penile cancers [50]. In recognition of these factors, the FDA approved Gardasil for the prevention of genital warts [51], anal cancer, and associated precancerous lesions in males in 2010 [36], The prophylactic prevention of HPV infection is clearly warranted regardless of sex, and the vaccination of males is regarded as a costeffective approach to reduce rates of HPV infection [52].…”
Section: Maximizing Vaccine Efficacymentioning
confidence: 99%